Development and validation of chemistry learning videos as learning media in the era of the COVID-19 pandemic - Amarulloh Amarulloh; Hisham Dzakiria (Journal of Sustainability Science and Technology, 2021)
Learning media, especially videos, are very effective in achieving learning objectives, especially during the COVID-19 pandemic. Therefore, this study aims to develop learning videos as learning media during the COVID-19 pandemic. The research was conducted using a development research approach from the Borg & Gall model. The developed product has good validity. Where the results of the content validation test by material experts show the CVR value in the range 0.75 – 0.95 (above the critical CVR value). The construct validity test results have a value in the range 0.75 – 0.95 so that it is included in the valid category. And lastly, the test results for student responses have percentage values in the range of 79% - 89% so that they are included in the interesting and very interesting category. Based on these results, the developed learning video can be used as a learning media solution during the COVID-19 pandemic.